The First Documented Case of Hb South Florida Variant in Portugal - Braga Martins, Marta (2022)
We present a 39-year-old male, previous smoker, with no other known cardiovascular risk factors. He was referred to Internal Medicine for study of thrombophilia, because of repeated deep vein thrombosis. Multiple diagnostic tests were undertaken where HbA1c assay was included. The result was 14.6%. The patient did not have a prior diagnosis of diabetes and denied any symptoms. Fasting blood glucose and blood count did not reveal any changes. A further analysis of hemoglobin subtypes showed the presence of an unclassified variant. The sample was sent to a Portuguese reference center and, through molecular biology, an HBB mutation in heterozygosity was identified, coding for an hemoglobin variant - Hb South Florida (c.4G > A; p.Val2Met), which was for the first time documented in Portugal. We emphasize the importance of considering the presence of hemoglobin variants when HbA1C values are discrepant from the clinical presentation.